Knockdown of S100A2 inhibits the aggressiveness of endometrial cancer by activating STING pathway - Chengcheng Li; Dandan Zhu; Xun Cao; Ying Li; Xiaoyuan Hao (Journal of Obstetrics and Gynaecology)
Background Endometrial cancer is a kind of gynaecological cancer. S100A2 is a newfound biomarker to diagnose endometrial cancer. This study was to investigate the role of S100A2 on regulating migration and invasion of endometrial cancer.Methods The mRNA and protein levels of S100A2 were obtained by quantitative real-time polymerase chain reaction, immunohistochemistry and western blot methods. Cell viability was measured by the Cell Counting Kit-8 assay. Cell migration and invasion were quantified using transwell assays. Western blot assay was conducted to quantify protein expressions of epithelial to mesenchymal transition-related proteins (N-cadherin and E-cadherin). Furthermore, in vivo tumour formation experiments were performed to evaluate the role of S100A2 on tumour xenografts.Results S100A2 was significantly up-regulated in endometrial cancer tissues. Knockdown of S100A2 inhibited cell viability, migration and invasion of endometrial cancer cells. Meanwhile, STING pathway was activated by the inhibited S100A2. STING inhibitor C-176 significantly reversed the effects of S100A2 knockdown on aggressive behaviours of endometrial cancer cells. Inhibition of S100A2 dramatically suppresses the tumour growth in vivo.Conclusions S100A2 functions as an oncogene in endometrial cancer. Targeting S100A2 may be a promising therapeutic method to treat endometrial carcinoma.